IMPLEMENTASI PENDIDIKAN AGAMA KRISTEN DALAM KELUARGA : PERAN ORANG TUA DALAM MEMBANGUN IMAN ANAK - Anerti Kase; Astryd Ndeo; Ivon Sine; Febrida Bani; Wandi Taneo (CV. ADIBA AISHA AMIRA, 2026)
Christian religious education in the family is very important in building children's faith, with parents as the primary educators of their children. In implementing PAK, besides church and school, the home becomes the main place for children to get to know Christ. In addition to teaching, the habits built in the family can make children's faith grow, such as worshiping together. Families who remain connected to God are empowered to live joyfully and without fear because they believe that God is Immanuel with them. Parental role modeling is very important in Christian education because children easily imitate what they see rather than what they hear. Parents must not be negligent in teaching and educating their children. Parents must continue to learn and strive to instill Christ-like character in their children through consistent daily activities at home. In this way, children's faith will grow and they will be able to live their lives according to God's Word, responding to and dealing with every dynamic of life by holding fast to God's Word. Character traits such as love, patience, honesty, diligence, and fear of God are what must be taught to children so that in their social relationships, wherever children are and interact, they reflect the character of Christ, and this becomes a sign that the parenting style and education of the parents determine the attitude of the child